The present situation about the teaching of Rorschach and other proyective tests in Peru - Ráez de Ramírez, Matilde (1999)
This papee presents a brief history about the origin and development of the proyecrive techniques in Peru. A questionnaire was administercd ro universitiy professors and members of the Peruvian Rorschach and Proyecrive Merhods Sociery in order ro collect data concerning the test rraining situation. Results indicare that there is a broad vicw towards scientific thought that stresses research and rhe use of standardized tests. lt is also pointed out, rhat the conceptual frame work is based on current changes in psychology.